Pendidikan Karakter Untuk Memperkuat Nilai-Nilai dalam Kehidupan Bermasyarakat dan Berbangsa - Faqih Purnomosidi; Trisna Rukhmana; Nur Hafida; Irsan Bertinus Tondowala; Septinus Wonggor; Aryo De Wibowo Muhammad Sidik (Departement of Mathematics Education, 2024)
Character education plays a major role in forming a strong moral and ethical foundation in social and national life. This research explores the implementation of character education in various societal and national contexts, evaluates its impact on students, and analyzes the factors that influence the success of the program. Case studies are used as research designs, involving educational participants, teachers and the community. The research results show variations in the implementation of character education, with positive responses from students towards the program. The role of involved teachers and community support are key factors in the success of the program, while challenges such as limited resources need to be overcome with adaptive strategies. In the discussion, the success factors and challenges faced in implementing character education are emphasized, providing insight for the development of more effective strategies. The conclusion highlights the vital role of character education in strengthening values ​​in social and national life, with implications for developing programs that are more inclusive and responsive to local needs.